Analisis Wacana pada Percakapan Film “Ice Cold: Murder, Coffee and Jessica Wongso” dalam Mempengaruhi Opini Publik - Ainun Fitri Mughiroh; Anwari; Slamet; Suhari (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
Public opinion can be formed or influenced through various media that contain it. Through documentary films, an event can be raised to be reviewed in a different form. One of them is a documentary film produced by Netflix with the title “Ice Cold: Murder, Coffee and Jessica Wongso”. The movie presents a collection of conversations and new facts that the public did not know before. The purpose of this research is to find out what forms of conversation in movies can shape and influence public opinion. This research uses the method of conversation analysis syntagmatic discourse analysis with the approach of perlocution speech act theory. The results of this study found 6 classifications of perlocutionary speech acts that are able to influence public opinion, namely anger, request, order, confusion, affirmation, annoyance